Molecular Alterations in Lung Adenocarcinoma With Ground-Glass Nodules: A Systematic Review and Meta-Analysis - Wei, Zihan; Wang, Ziyang; Nie, Yuntao; Zhang, Kai; Shen, Haifeng; Wang, Xin; Wu, Manqi; Yang, Fan; Chen, Kezhong (Frontiers in Oncology, 2021)
Background and aims: Nodular ground-glass lesions have become increasingly common with the increased use of computed tomography (CT), while the genomic features of ground-glass opacities (GGOs) remain unclear. This study aims to comprehensively investigate the molecular alterations of GGOs and their correlation with radiological progression. Methods: Studies from PubMed, Embase, Cochrane Library, and Web of Science, using PCR, targeted panel sequencing, whole exosome sequencing, and immunohistochemistry, and reporting genomic alterations or PD-L1 expressions in lung nodules presenting as GGOs until January 21st, 2021, were included in this study. Chi-square test, random-effects model, and Z-test analysis were adopted to analyze the data. Results: Twenty-two studies describing mutations in lung adenocarcinoma (LUAD) with GGOs were analyzed. EGFR was the most frequently mutative gene (51%，95%CI 47%-56%), followed by TP53 (18%, 95%CI 6%-31%), HER2 (10%, 95%CI 0%-21%), ROS1 (6%, 95%CI 0%-18%), KRAS (6%, 95%CI 3%-9%). The correlation between the frequency of EGFR mutation and radiological was observed and the differences were found to be not statistically significant in subgroups, which are listed as below: radiological: pGGO 47.40%, 95%CI [38.48%; 56.40%]; mGGO 51.94%, 95%CI [45.15%; 58.69%]. The differences of the frequency of KRAS mutation in different subgroups were also consistent with this conclusion, which are listed as below: radiological pGGO 3.42, 95%CI [1.35%; 6.13%]; mGGO 12.27%, 95%CI [3.89%; 23.96%]. The pooled estimated rate of PD-L1 was 8.82%, 95%CI [5.20%-13.23%]. 11.54% (3/26) SMGGNs were confirmed to be intrapulmonary spread by WES. Conclusions: Somatic genetic alterations are considered in early-stage GGO patients without distinct changes of the frequency following the progress of the tumor. This review sheds insight on molecular alterations in LUAD with GGOs.